WATERMARKING IN IMAGE USING SLANTLET TRANSFORM - Lafta, Muna; Alwan, Iman (Iraqi Journal of Science, 2024)
A watermarking scheme based on slantlet transform, an orthogonal discretewavelet transform with two zero moments and with improved time localization, ispresented in this paper. The watermark is embedded into mid band frequencies ofslantlet coefficients in the transform domain, which leads to very small distortionand guarantees the visual quality of the watermarked image. The performance of theproposed algorithm is compared with embedding watermarking system usingwavelet transformation the result show promising performance of the proposedsystem where the increasing in PSNR is approximately 20 dB.